Evaluasi Pelayanan Kesehatan Reproduksi Bagi Pengungsi Rawan Bencana Erupsi Merapi - Siti Nuruniyah (Alma Ata University Press, 2016)
Condition refuge causes several issues on health reproduction such as violence and sexual abuse, unsafe sexual intercourse, contraceptive distribution problems, coordination across programs and across sectors are unoptimal, and the person in charge of the organizational structure are not clear and not all health workers health providers trained. To overcome these problems and provide ideal reproductive health services for refugees needed strategies to achieve them. The strategy formulated from the results of the SWOT analysis of input, process and output Sleman District Health Ofﬁ ce.